2008
DOI: 10.1007/s10623-008-9206-6
|View full text |Cite
|
Sign up to set email alerts
|

Attacks on the RC4 stream cipher

Abstract: In this article we present some weaknesses in the RC4 cipher and their cryptographic applications. Especially we improve the attack described in [2] in such a way, that it will work, if the weak keys described in that paper are avoided. A further attack will work even if the first 256 Byte of the output remain unused. Finally we show that variants of the RC4 algorithm like NGG and RC4A are also vulnerable by these techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(76 citation statements)
references
References 9 publications
0
76
0
Order By: Relevance
“…• In Section 3.3, we observe new biases in the initial keystream bytes apart from the known ones [5]. It is shown that for 3 ≤ r ≤ 32, P (z r = f r−1 ) are not random associations.…”
Section: Notations Contributions and Outlinementioning
confidence: 90%
See 4 more Smart Citations
“…• In Section 3.3, we observe new biases in the initial keystream bytes apart from the known ones [5]. It is shown that for 3 ≤ r ≤ 32, P (z r = f r−1 ) are not random associations.…”
Section: Notations Contributions and Outlinementioning
confidence: 90%
“…Some results for biases in initial keystream bytes has earlier been pointed out in [5] that has later been discussed in [19] too. We detail these biases giving explicit formula under our theoretical framework.…”
mentioning
confidence: 83%
See 3 more Smart Citations